Factors influencing the success of learning management system (LMS) on students’ academic performance - Dzulkaman, Nur Sakinah; Mohamad Ali, Afiza (Kulliyyah of Languages and Management (KLM) , International Islamic University Malaysia (IIUM), 2016)
E-learning systems have gained substantial attention in the educational world.One of them is the Learning Management System (LMS), a pedagogical platform that is based on web technology. The LMS enables instructors to share materials, organize lessons and assessments, and virtually communicate with students to support the learning and teaching process. The aim of this study is to investigate the factors related to LMS that influence students’ academic performance. Quantitative data from 20 respondents at a large Malaysian university are obtained from a 12-item questionnaire. Findings showed that effectiveness of the LMS system and students’ motivation significantly correlated with their academic performance success. The findings suggest that instructors need to pay a greater role in motivating students to use the LMS via innovative and creative means.